ANALISIS TINGKAT KEMAMPUAN MEMBACA PEMAHAMAN SISWA DALAM MEMAHAMI MATERI TEKS DESKRIPTIF SISWA KELAS 4 - Utami Kusdiani, Siti; Sukma Nugraha, Widdy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is driven by the importance of literacy within the Kurikulum Merdeka framework, where reading comprehension skills serve as a primary determinant of academic success for elementary school students. The study aims to comprehensively describe the level of reading comprehension in descriptive text materials among fourth-grade students at SDN 2 Pananjung. A descriptive quantitative method with a survey design was employed. The research population consisted of all 29 fourth-grade students at SDN 2 Pananjung, who were selected as respondents through a total sampling technique. The research instrument utilized a questionnaire constructed based on literal, inferential, and evaluative reading comprehension indicators. Descriptive statistical techniques were used for data analysis to determine frequency distribution and student percentage levels. The findings indicate that the majority of students possess reading comprehension skills in the high category, specifically 22 students (75.9%). Meanwhile, 6 students (20.7%) were in the medium category, and only 1 student (3.4%) was in the low category. These results reflect that the fourth-grade students at SDN 2 Pananjung are capable of integrating both literal and in-depth textual understanding of descriptive texts, suggesting the effectiveness of the literacy instructional process at the school.